Comparative and Evolutionary Analyses on the Complete Plastomes of Five Kalanchoe Horticultural Plants - Tian, Xiangyu; Guo, Jia; Zhou, Xiaojiao; Ma, Ke; Ma, Yonggui; Shi, Tuansheng; Shi, Yuhua (Frontiers in Plant Science, 2021)
Many species of the genus Kalanchoe are important horticultural plants. They have evolved the CAM (Crassulacean acid metabolism) photosynthetic pathway to allow them to be better adapted to dry environments. Despite their importance, it is still debating whether Kalanchoe is monophyletic, and understanding the past diversification of this genus requires a tremendous amount of efforts and work being devoted to the studies of morphological and molecular characters of this genus. However, molecular information, plastic sequence data in particular, reported on Kalanchoe species is scarce, and this has posed a great challenge on trying to interpret the evolutionary history of this genus. In this study, plastomes of the five Kalanchoe species, including K. daigremontiana, K. delagoensis, K. fedtschenkoi, K. longiflora, and K. pinnata, were sequenced and analyzed. The results indicate that the five plastomes are comparable in size, GC contents and number of genes, which also demonstrate insignificant difference in comparison with other species from the family Crassulaceae. 224 simple sequence repeats (SSRs) and 144 long repeats were identified in the five plastomes, and most of these are distributed in the inverted repeat (IR) regions. In addition, highly divergent regions containing either SNPs (single nucleotide polymorphism) or InDel (insertion or deletion) mutations are discovered, which could be potentially used for establishing phylogenetic relationship among members of the Kalanchoe genus in future studies. Moreover, phylogenetic analyses suggest that Bryophyllum should be placed into one single genus as Kalanchoe. Further genomic analyses also reveal that a number of genes are undergone positive selection. Among them, eleven genes are involved in important cellular processes, such as cell survival, electron transfer, etc., and may have played indispensable roles in the adaptive evolution of Kalanchoe to dry environments.